Improving screening and brief intervention activities in primary health care: Secondary analysis of professional accuracy based on the AUDIT‐C. Issue 2 (1st December 2017) - Palacio‐Vieira, J.; Segura, L.; Anderson, P.; Wolstenholme, A.; Drummond, C.; Bendtsen, P.; Wojnar, M.; Kaner, E.; Keurhorst, M.N.; van Steenkiste, B.; Kłoda, K.; Mierzecki, A.; et al.
Abstract: Introduction and objective: The ODHIN trial found that training and support and financial reimbursement increased the proportion of patients that were screened and given advice for their heavy drinking in primary health care. However, the impact of these strategies on professional accuracy in delivering screening and brief advice is underresearched and is the focus of this paper. Method: From 120 primary health care units (24 in each jurisdiction: Catalonia, England, the Netherlands, Poland, and Sweden), 746 providers participated in the baseline and the 12‐week implementation periods. Accuracy was measured in 2 ways: correctness in completing and scoring the screening instrument, AUDIT‐C; the proportion of screen‐negative patients given advice, and the proportion of screen‐positive patients not given advice. Odds ratios of accuracy were calculated for type of profession and for intervention group: training and support, financial reimbursement, and internet‐based counselling. Results: Thirty‐two of 36 711 questionnaires were incorrectly completed, and 65 of 29 641 screen‐negative patients were falsely classified. At baseline, 27% of screen‐negative patients were given advice, and 22.5% screen‐positive patients were not given advice. These proportions halved during the 12‐week implementation period, unaffected by training. Financial reimbursement reduced the proportion of screen‐positive patients not given advice (OR = 0.56; 95% CI, 0.31‐0.99; P  < .05). Conclusion: Although the use of AUDIT‐C as a screening tool was accurate, a considerable proportion of risky drinkers did not receive advice, which was reduced with financial incentives.